Expressway pavement anti-crack repairing material and preparation method thereof

By using crack-resistant repair materials containing composite crack-resistant fillers on fast road pavements, the problem of reduced strength and durability caused by pavement cracks is solved, and higher crack resistance and durability are achieved.

CN119613016AActive Publication Date: 2025-03-14YANCHENG ROAD MAINTENANCE EMERGENCY RESPONSE CENT +1
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411549853.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-03-14
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

Due to the existence of cracks on the express highway pavement, the strength and durability of the pavement are reduced, affecting traffic safety and service life. There is room for improvement in crack resistance of existing crack-resistant asphalt mixtures, especially poor compatibility between impermeable fibers and asphalt matrix.

Method used

A fast road pavement crack-resistant repair material is used, including asphalt, gravel, quartz sand, ore powder and composite crack-resistant filler. The composite crack-resistant filler generates hydroxy-terminated polycaprolactone through the ring-opening polymerization of ε-caprolactone and pentaerythritol, and is coated with glass fibers, combined with bisphenol A type epoxy vinyl ester resin, and improves mechanical properties and adhesiveness through chemical reactions.

Benefits of technology

The low-temperature crack resistance, high-temperature stability, mechanical strength and bonding effect of the crack-resistant repair materials on the expressway pavement are significantly improved, and the risk of fracture and the probability of crack recurrence is reduced, thereby improving the durability of the pavement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005114778860000081
    Figure BDA0005114778860000081
Patent Text Reader

Abstract

The invention discloses an expressway pavement anti-crack repair material and a preparation method thereof, and belongs to the technical field of pavement repair, the expressway pavement anti-crack repair material comprises the following components by weight: 5-10 parts of asphalt, 10-20 parts of gravel, 30-50 parts of quartz sand, 30-50 parts of a composite anti-crack filler, and 10-20 parts of mineral powder. The asphalt, the gravel, the quartz sand, the mineral powder and the composite anti-crack filler are adopted, and the bonding effect of the composite anti-crack filler is matched with the filling effect of the powder, so that the structural compactness of the anti-crack repairing material for the expressway pavement is further improved; therefore, the low-temperature crack resistance, the high-temperature stability, the mechanical strength and the bonding effect of the anti-crack repairing material for the expressway pavement are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of road surface repair, and in particular to an expressway road surface crack-resistant repair material and a preparation method thereof. Background Art

[0002] With the rapid development of my country's economy, highway construction has also entered a period of rapid development. As an important traffic artery, the road quality of expressways has an important impact on the safety and service life of road traffic. With the increase of vehicle load and the increase of the service life of expressways, expressways are seriously damaged. Cracks are one of the main diseases of expressways. Due to the existence of cracks, the strength and durability of the road surface are seriously reduced, the flatness index is reduced, the driving comfort is affected, and the traffic safety is seriously affected, and the normal use and safe operation of expressways cannot be guaranteed.

[0003] Chinese patent document CN115716725A discloses a crack-resistant asphalt mixture and its preparation method, which belongs to the field of road engineering technology. The mixture includes by weight: 7-10 parts of matrix asphalt, 60-70 parts of coarse aggregate, 25-35 parts of fine aggregate, 4.5-6 parts of impermeable fiber filler, 3-5 parts of reinforced node filler, 5-8 parts of mineral powder, and 2-3 parts of asphalt oil. The impermeable fiber filler and the reinforced node filler are compounded, and after paving, an interactive network structure with certain elasticity and water absorption and expansion performance is formed in the road surface, which resists the deformation and cracking of the road surface, and at the same time absorbs water and expands to fill the gaps in the road surface, avoiding water from penetrating into the road surface to generate dynamic water pressure and pumping, and preventing the road surface from deteriorating sharply after the initial aging cracks; there is poor compatibility between the impermeable fiber filler and the asphalt matrix in the invention, resulting in further improvement in its crack resistance. Summary of the invention

[0004] The main purpose of the invention is to provide an expressway pavement crack-resistant repair material with good crack-resistant performance.

[0005] To achieve the above objectives, the present invention proposes an expressway pavement anti-cracking repair material, which comprises the following components, by weight: 5-10 parts of asphalt, 10-20 parts of crushed stone, 30-50 parts of quartz sand, 30-50 parts of composite anti-cracking filler, and 10-20 parts of mineral powder.

[0006] Preferably, the crushed stone particle size is 10-30 mm.

[0007] Preferably, the preparation method of the composite anti-cracking filler is as follows:

[0008] 1) In an Ar2 atmosphere, ε-caprolactone and pentaerythritol are mixed, and then a ring-opening polymerization reaction is carried out under the catalytic conditions of a catalyst to generate a hydroxyl-terminated polycaprolactone;

[0009] 2) mixing hydroxyl-terminated polycaprolactone, crotonic anhydride and toluene and heating them under acidic conditions for reaction, and after the reaction is completed, immersing the glass fiber in the reaction solution, taking out the glass fiber, and drying it to obtain the polycaprolactone-coated glass fiber;

[0010] 3) mixing bisphenol A epoxy vinyl ester resin and polycaprolactone coated glass fiber, heating and stirring to obtain a mixture; after the temperature of the mixture is cooled, adding ethylenediamine and azobisisobutyronitrile to the mixture, mixing and stirring to obtain the composite anti-cracking filler.

[0011] Preferably, the catalyst in step 1) is stannous isooctanoate.

[0012] Preferably, in step 1), the mass ratio of ε-caprolactone to pentaerythritol is 70-90:1.

[0013] Preferably, in the step 2), the mass ratio of the hydroxyl-terminated polycaprolactone, crotonic anhydride and glass fiber is 100:8-10:5-8; the heating temperature is 60-80° C., and the reaction time is 2-4 hours.

[0014] The preparation of the polycaprolactone coated glass fiber is first to generate hydroxyl-terminated polycaprolactone by ring-opening polymerization of ε-caprolactone, and then the hydroxyl-terminated polycaprolactone reacts with crotonic anhydride under acidic conditions to obtain polycaprolactone containing carbon-carbon double bonds, and then the glass fiber is immersed in the polycaprolactone solution containing carbon-carbon double bonds. The polycaprolactone solution containing carbon-carbon double bonds can be coated on the surface of the glass fiber, which is beneficial to subsequent reactions on the one hand, and on the other hand, the elastomer polycaprolactone can synergistically improve the toughness of the composite anti-cracking filler with the glass fiber, thereby improving the anti-cracking performance of the anti-cracking repair material for expressway pavement.

[0015] Preferably, in the step 3), the mass ratio of epoxy vinyl ester resin, polycaprolactone coated glass fiber, ethylenediamine and azobisisobutyronitrile is 60-80:10-15:10-20:2-4; the vacuum degassing treatment conditions are a vacuum degree of -0.01 to -0.09 MPa and a degassing time of 3-5 min.

[0016] Preferably, the curing temperature is 60-100°C.

[0017] Bisphenol A epoxy vinyl ester resin is an adhesive with good corrosion resistance. Both ends of its molecular chain are active carbon-carbon double bonds. Under the action of azobisisobutyronitrile, it reacts with polycaprolactone coated glass fiber to produce an addition reaction. The polycaprolactone coated glass fiber is introduced into the structure of bisphenol A epoxy vinyl ester resin through chemical reaction, which is beneficial to improve the mechanical properties of bisphenol A epoxy vinyl ester resin. Due to the good adhesion of bisphenol A epoxy vinyl ester resin, the polycaprolactone coated glass fiber can be better dispersed and filled in the anti-cracking repair material of the expressway pavement, so that the anti-cracking repair material of the expressway pavement can significantly reduce the risk of fracture when it is run over by vehicles, reducing the probability of cracks on the expressway pavement again, thereby improving the durability of the expressway.

[0018] Preferably, the particle size of the mineral powder is 0.2-1 mm.

[0019] The present invention also discloses a method for preparing the above-mentioned expressway pavement anti-cracking repair material, comprising the following steps: weighing each component according to a formula, mixing asphalt and a composite anti-cracking filler, heating and stirring to obtain a slurry, adding crushed stone, quartz sand, and mineral powder to the slurry, stirring and mixing evenly to obtain the expressway pavement anti-cracking repair material.

[0020] Preferably, the heating temperature is 120-150° C. and the stirring time is 3-5 h.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] (1) The present invention uses asphalt, crushed stone, quartz sand, mineral powder, and composite anti-cracking filler, and utilizes the bonding effect of the composite anti-cracking filler in combination with the filling effect of the powder to further improve the structural density of the anti-cracking repair material for the expressway pavement, thereby improving the low-temperature crack resistance, high-temperature stability, mechanical strength, and bonding effect of the anti-cracking repair material for the expressway pavement;

[0023] (2) The composite anti-cracking fiber of the present invention is prepared by introducing polycaprolactone coated glass fiber into the structure of bisphenol A epoxy vinyl ester resin through chemical reaction, which is beneficial to improving the mechanical properties of bisphenol A epoxy vinyl ester resin; through the good adhesion of bisphenol A epoxy vinyl ester resin, the polycaprolactone coated glass fiber can be better dispersed and filled in the anti-cracking repair material of the expressway pavement, thereby improving the structural density of the anti-cracking repair material of the expressway pavement, and making the anti-cracking repair material of the expressway pavement can significantly reduce the risk of fracture when being crushed by a vehicle, thereby reducing the probability of cracks occurring again on the expressway pavement, thereby improving the durability of the expressway. DETAILED DESCRIPTION

[0024] To avoid redundancy, the items used in the following examples are all commercially available products unless otherwise specified, and the methods used are all conventional methods unless otherwise specified.

[0025] The sources of some raw materials used in the present invention are as follows:

[0026] Asphalt, softening point 75.3℃, elongation 32.5cm at 5℃, elongation 100cm at 15℃, needle penetration 52.3mm, model 10#, Shenzhen Zhongheng Asphalt Engineering Co., Ltd.

[0027] Bisphenol A epoxy vinyl ester resin, brand DM411-350, was purchased from Shandong Deshang Chemical Co., Ltd.

[0028] Example 1

[0029] A method for preparing an anti-cracking repair material for an expressway pavement comprises the following steps: mixing 80 g of asphalt and 400 g of a composite anti-cracking filler, stirring the mixture at 140° C. for 4 hours to obtain a slurry, adding 150 g of crushed stone, 400 g of quartz sand, and 150 g of mineral powder to the slurry, and stirring the mixture to obtain the anti-cracking repair material for an expressway pavement.

[0030] The preparation method of the composite anti-cracking filler is as follows:

[0031] 1) Under Ar2 atmosphere, 160g of ε-caprolactone and 2g of pentaerythritol were mixed, heated to 80°C, 1.6g of stannous isooctanoate was added, and the mixture was reacted for 24h; after the reaction was completed, the mixture was cooled to 30°C, filtered, the solid was dissolved with 800mL of dichloromethane, and 800mL of anhydrous methanol was added; after stirring for 20-30min, the mixture was filtered, the solid was collected and dried to obtain hydroxyl-terminated polycaprolactone;

[0032] 2) 100 g of hydroxyl-terminated polycaprolactone, 8.8 g of crotonic anhydride, 500 mL of toluene, and 2 g of p-toluenesulfonic acid were mixed and heated at 70° C. for 3 h. After the reaction, 30 g of glass fiber was immersed in the reaction solution for 5 h. The glass fiber was taken out and dried to obtain polycaprolactone-coated glass fiber;

[0033] 3) 70 g of bisphenol A epoxy vinyl ester resin and 13.5 g of polycaprolactone coated glass fiber were mixed and stirred at 60° C. to obtain a mixture; when the temperature of the mixture was cooled to 30° C., 15 g of ethylenediamine and 3 g of azobisisobutyronitrile were added to the mixture, the mixture was mixed and stirred evenly, and then vacuum degassing was performed at -0.05 MPa for 4 min and cured at 80° C. to obtain the composite anti-cracking filler.

[0034] Example 2

[0035] A method for preparing an anti-cracking repair material for an expressway pavement comprises the following steps: mixing 50 g of asphalt and 300 g of a composite anti-cracking filler and stirring the mixture at 120° C. for 3 h to obtain a slurry; adding 100 g of crushed stone, 300 g of quartz sand and 100 g of mineral powder to the slurry; and stirring the mixture to obtain the anti-cracking repair material for an expressway pavement.

[0036] The preparation method of the composite anti-cracking filler is as follows:

[0037] 1) Under Ar2 atmosphere, 140g of ε-caprolactone and 2g of pentaerythritol were mixed, heated to 60°C, 1.4g of stannous isooctanoate was added, and the mixture was reacted for 20h; after the reaction was completed, the mixture was cooled to 30°C, filtered, the solid was dissolved with 500mL of dichloromethane, and 1000mL of anhydrous methanol was added; after stirring for 20min, the mixture was filtered, the solid was collected and dried to obtain hydroxyl-terminated polycaprolactone;

[0038] 2) 100 g of hydroxyl-terminated polycaprolactone, 8 g of crotonic anhydride, 500 mL of toluene, and 2 g of p-toluenesulfonic acid were mixed and heated at 60° C. for 2 h. After the reaction, 30 g of glass fiber was immersed in the reaction solution for 5 h. After the immersion was completed, the glass fiber was taken out and dried to obtain polycaprolactone-coated glass fiber;

[0039] 3) 60 g of bisphenol A epoxy vinyl ester resin and 10 g of polycaprolactone coated glass fiber are mixed and stirred at 50° C. to obtain a mixture; when the temperature of the mixture is cooled to 30° C., 10.2 g of ethylenediamine and 2.1 g of azobisisobutyronitrile are added to the mixture, the mixture is mixed and stirred evenly, and then vacuum degassing is performed at -0.01 MPa for 5 min and cured at 60° C. to obtain the composite anti-cracking filler.

[0040] Example 3

[0041] A method for preparing an anti-cracking repair material for an expressway pavement comprises the following steps: mixing 100 g of asphalt and 500 g of a composite anti-cracking filler, stirring the mixture at 150° C. for 5 h to obtain a slurry, adding 200 g of crushed stone, 500 g of quartz sand and 200 g of mineral powder to the slurry, and stirring the mixture to obtain the anti-cracking repair material for an expressway pavement.

[0042] The preparation method of the composite anti-cracking filler is as follows:

[0043] 1) Under Ar2 atmosphere, 180g of ε-caprolactone and 2g of pentaerythritol were mixed, heated to 100°C, 1.8g of stannous isooctanoate was added, and the mixture was reacted for 24h; cooled to 30°C, filtered, the solid was dissolved with 1000mL of dichloromethane, 1000mL of anhydrous methanol was added, stirred for 30min, filtered, the solid was collected and dried to obtain hydroxyl-terminated polycaprolactone;

[0044] 2) 100 g of hydroxyl-terminated polycaprolactone, 10 g of crotonic anhydride, 500 mL of toluene, and 2.2 g of p-toluenesulfonic acid were mixed and heated at 80° C. for 4 h. After the reaction, 30 g of glass fiber was immersed in the reaction solution for 5 h. After the immersion was completed, the glass fiber was taken out and dried to obtain polycaprolactone-coated glass fiber;

[0045] 3) 80 g of bisphenol A epoxy vinyl ester resin and 15 g of polycaprolactone coated glass fiber are mixed and stirred at 70° C. to obtain a mixture; when the temperature of the mixture is cooled to 30° C., 20 g of ethylenediamine and 4 g of azobisisobutyronitrile are added to the mixture, the mixture is mixed and stirred evenly, and then vacuum degassing is performed at -0.09 MPa for 3 min and cured at 100° C. to obtain the composite anti-cracking filler.

[0046] Comparative Example 1

[0047] A method for preparing an anti-cracking repair material for an expressway pavement is similar to that of Example 1, except that the composite anti-cracking filler is polycaprolactone-coated glass fiber, and specifically comprises the following steps: 80 g of asphalt and 400 g of the composite anti-cracking filler are mixed, and the mixture is stirred at 140° C. for 4 hours to obtain a slurry; 150 g of crushed stone, 400 g of quartz sand, and 150 g of mineral powder are added to the slurry, and the mixture is stirred and mixed evenly to obtain the anti-cracking repair material for an expressway pavement.

[0048] The preparation method of the composite anti-cracking filler is as follows:

[0049] 1) Under Ar2 atmosphere, 160g of ε-caprolactone and 2g of pentaerythritol were mixed, heated to 80°C, 1.6g of stannous isooctanoate was added, and the mixture was reacted for 24h; after the reaction was completed, the mixture was cooled to 30°C, filtered, the solid was dissolved with 800mL of dichloromethane, and 800mL of anhydrous methanol was added; after stirring for 20-30min, the mixture was filtered, the solid was collected and dried to obtain hydroxyl-terminated polycaprolactone;

[0050] 2) 100 g of hydroxyl-terminated polycaprolactone, 8.8 g of crotonic anhydride, 500 mL of toluene, and 2 g of p-toluenesulfonic acid were mixed and heated at 70°C for reaction for 3 h. After the reaction, 30 g of glass fiber was immersed in the reaction solution for 5 h. The glass fiber was taken out and dried to obtain polycaprolactone-coated glass fiber, which is a composite anti-cracking filler.

[0051] Comparative Example 2

[0052] A method for preparing an anti-cracking repair material for an expressway pavement is similar to that of Example 1, except that the composite anti-cracking filler is a mixture of bisphenol A epoxy vinyl ester resin and glass fiber, and specifically comprises the following steps: 80 g of asphalt and 400 g of the composite anti-cracking filler are mixed, and the mixture is stirred at 140° C. for 4 hours to obtain a slurry; 150 g of crushed stone, 400 g of quartz sand, and 150 g of mineral powder are added to the slurry, and the mixture is stirred and mixed evenly to obtain the anti-cracking repair material for an expressway pavement.

[0053] The preparation method of the composite anti-cracking filler is as follows:

[0054] 70 g of bisphenol A epoxy vinyl ester resin and 13.5 g of glass fiber are mixed and stirred at 60° C. to obtain a mixture; when the temperature of the mixture is cooled to 30° C., 15 g of ethylenediamine and 3 g of azobisisobutyronitrile are added to the mixture, the mixture is mixed and stirred evenly, and then vacuum degassing treatment is performed at -0.05 MPa for 4 minutes and cured at 80° C. to obtain the composite anti-cracking filler.

[0055] Performance Testing

[0056] Freeze-thaw splitting test: The test objects are the anti-cracking repair materials for expressway pavement prepared in Examples 1-3 and Comparative Examples 1-2. The freeze-thaw splitting strength of the anti-cracking repair materials is detected and the data is recorded according to the freeze-thaw splitting test of asphalt mixture T0729-2000 in CJJ / T190-2012 "Technical Specifications for Permeable Asphalt Pavement" and JTG E20-2011 "Test Specifications for Asphalt and Asphalt Mixtures for Highway Engineering". The freeze-thaw splitting test characterizes the low-temperature crack resistance of the anti-cracking repair materials. The test results are shown in Table 1:

[0057] Kentaburg scattering test: The test objects are the anti-cracking repair materials for the expressway pavement prepared in Examples 1-3 and Comparative Examples 1-2. Referring to the Kentaburg scattering test for asphalt mixture T0733-2011 in CJJ / T190-2012 "Technical Specifications for Permeable Asphalt Pavement" and JTG E20-2011 "Test Specifications for Asphalt and Asphalt Mixtures for Highway Engineering", the formed Marshall specimens (compacted 50 times on both sides) were subjected to the Kentaburg scattering test to record the scattering rate data; the Kentaburg scattering test is used to detect the degree of aggregate shedding and loss on the road surface of the anti-cracking repair materials for expressway pavement under traffic loads, and to characterize the mechanical strength and bonding effect of the anti-cracking repair materials for expressway pavement; the test results are shown in Table 1:

[0058] Rutting test: The test objects are the anti-cracking repair materials for expressway pavement prepared in Examples 1-3 and Comparative Examples 1-2. The rutting test for asphalt mixtures in CJJ / T190-2012 "Technical Specifications for Permeable Asphalt Pavement" and JTG E20-2011 "Test Specifications for Asphalt and Asphalt Mixtures for Highway Engineering" is referred to. The rutting test is carried out at 60°C and 0.7MPa, and the dynamic stability data is recorded; the high temperature stability of the anti-cracking repair materials is characterized; the test results are shown in Table 1:

[0059] Table 1 Test results of performance of anti-crack repair materials for expressway pavement

[0060]

[0061] It can be seen from the experimental results in Table 1 that the expressway pavement crack resistance repair material prepared by the present invention has good low-temperature crack resistance, high-temperature stability, mechanical strength and bonding effect.

[0062] The above are only preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.

Claims

1. An anti-crack repair material for expressway pavement, characterized in that: The composition includes the following components in parts by weight: 5-10 parts of asphalt, 10-20 parts of crushed stone, 30-50 parts of quartz sand, 30-50 parts of composite anti-cracking filler, and 10-20 parts of mineral powder.

2. The anti-crack repair material for expressway pavement according to claim 1, characterized in that: The crushed stone particle size is 10-30 mm.

3. The anti-crack repair material for expressway pavement according to claim 1, characterized in that: The preparation method of the composite anti-cracking filler is as follows: 1) In an Ar2 atmosphere, ε-caprolactone and pentaerythritol are mixed, and then a ring-opening polymerization reaction is carried out under the catalytic conditions of a catalyst to generate a hydroxyl-terminated polycaprolactone; 2) mixing hydroxyl-terminated polycaprolactone, crotonic anhydride and toluene and heating them under acidic conditions for reaction, and after the reaction is completed, immersing the glass fiber in the reaction solution, taking out the glass fiber, and drying it to obtain the polycaprolactone-coated glass fiber; 3) mixing bisphenol A epoxy vinyl ester resin and polycaprolactone coated glass fiber, heating and stirring to obtain a mixture; after the temperature of the mixture is cooled, adding ethylenediamine and azobisisobutyronitrile to the mixture, mixing and stirring to obtain the composite anti-cracking filler.

4. The anti-crack repair material for expressway pavement according to claim 3, characterized in that: In the step 1), the catalyst is stannous isooctanoate.

5. The anti-crack repair material for expressway pavement according to claim 3, characterized in that: In the step 1), the mass ratio of ε-caprolactone to pentaerythritol is 70-90:

1.

6. The anti-crack repair material for expressway pavement according to claim 3, characterized in that: In the step 2), the mass ratio of the hydroxyl-terminated polycaprolactone, crotonic anhydride and glass fiber is 100:8-10:5-8.

7. The anti-crack repair material for expressway pavement according to claim 3, characterized in that: In the step 2), the heating temperature is 60-80° C. and the reaction time is 2-4 hours.

8. The anti-crack repair material for expressway pavement according to claim 3, characterized in that: In the step 3), the mass ratio of epoxy vinyl ester resin, polycaprolactone coated glass fiber, ethylenediamine and azobisisobutyronitrile is 60-80:10-15:10-20:2-4.

9. The anti-crack repair material for expressway pavement according to claim 1, characterized in that: The particle size of the mineral powder is 0.2-1 mm.

10. A method for preparing the anti-cracking repair material for expressway pavement according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: weighing each component according to a formula, mixing asphalt and composite anti-cracking filler, heating and stirring to obtain slurry, adding crushed stone, quartz sand and mineral powder into the slurry, stirring and mixing evenly to obtain the expressway pavement anti-cracking repair material.

Citation Information

Patent Citations

  • Anti-crack asphalt mixture and preparation method thereof

    CN115716725A

  • Directional orifice oxide material and preparation method thereof

    CN101555157A

  • Anti-crack cold-mixed asphalt for pavement repair and preparation method thereof

    CN114276051A

  • Transient zinc ion battery and preparation method and application thereof

    CN116864639A

  • Lifting hanger with good stability

    CN221319056U